2014
DOI: 10.1155/2014/320906
|View full text |Cite
|
Sign up to set email alerts
|

Purinergic Receptors in Ocular Inflammation

Abstract: Inflammation is a complex process that implies the interaction between cells and molecular mediators, which, when not properly “tuned,” can lead to disease. When inflammation affects the eye, it can produce severe disorders affecting the superficial and internal parts of the visual organ. The nucleoside adenosine and nucleotides including adenine mononucleotides like ADP and ATP and dinucleotides such as P1,P4-diadenosine tetraphosphate (Ap4A), and P1,P5-diadenosine pentaphosphate (Ap5A) are present in differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 96 publications
0
33
0
Order By: Relevance
“…Thus, a common pathogenic growth factor-κB-TNF-α (NF-kB-TNF-α) signaling pathway, the inhibition of cytokines secretion, and the apoptosis of inflammatory cells [73]. It has been suggested that the improvement of several pathological signs and symptoms in subjects with DE, such as Schirmer test and BUT scores, might be due to reduced ocular surface's inflammation following direct interaction between CF101 and its receptors on inflammatory cells [73].…”
Section: Up To Date On Biochemical Mechanisms In Dry Eye Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, a common pathogenic growth factor-κB-TNF-α (NF-kB-TNF-α) signaling pathway, the inhibition of cytokines secretion, and the apoptosis of inflammatory cells [73]. It has been suggested that the improvement of several pathological signs and symptoms in subjects with DE, such as Schirmer test and BUT scores, might be due to reduced ocular surface's inflammation following direct interaction between CF101 and its receptors on inflammatory cells [73].…”
Section: Up To Date On Biochemical Mechanisms In Dry Eye Diseasementioning
confidence: 99%
“…An equilibrate balance between ω3 and ω6 is necessary to avoid the prevalence of ω6 proinflammatory effect. In particular, proresolving lipid mediators derived from ω-3 precursors, such as docosahexaenoic acid (DHA) and eicopentaenoic acid (EPA), control epithelial wound healing, inflammatory cell migration, and nerve regeneration [74,75] subsequent generation of eicosanoid lipid mediators is responsible to trigger the acute inflammatory response to corneal injury [73]. But, its resolution is mediated by proresolving lipid mediators derived from ω-3 PUFA precursors, DHA and EPA.…”
Section: Up To Date On Biochemical Mechanisms In Dry Eye Diseasementioning
confidence: 99%
“…P2X2R is present in the trigeminal ganglion sensory neurons and ciliary body. 112 In chronic glaucoma, ATP is released through pannexin hemichannels in astrocytes of the optic nerve and activates P2X7Rs that can increase cell death in the retina. The ATP release from astrocytes can result from chronic mechanical strain (stretch) as it occurs in glaucoma through the upregulation of pannexins.…”
Section: P2xr Modulators As Drug Targets In the Eyementioning
confidence: 99%
“…20,21,72,73 The purinergic system is fully represented in this part of the eye since apart from the presence of these receptors, the existence of enzymes responsible for the degradation of nucleotides, a nucleotide vesicular transporter, has also been detected. 74 Altogether nucleotides and dinucleotides may play important roles acting in the retina as autocrine and paracrine mediators.…”
Section: Ap 4 a In The Retina Nothing At Allmentioning
confidence: 99%